Failure analysis on hybrid fiber reinforced plastics for bolted joint under geometric parameters effect - Sivakumar, Dhar Malingam; Selamat, Mohd Zulkefli; Ahadlin, Mohd Daud; Tan, CheeFai (2016)
In this study, glass fiber and kenaf reinforced thermoplastic hybrid composite were fabricated using compression method. The composite is layout in sandwich structure. Woven glass fiber is sandwiched in between woven kenaf fiber with polypropylene matrix. The nominal thickness of the composite is 3mm. Bolted joint test was conducted according to ASTM D5961 using Universal testing machine. The results confirm geometric parameters affect the failure mode.